Therapeutic benefit of apremilast on enthesitis and dactylitis in patients with psoriatic arthritis: a pooled analysis of the PALACE 1–3 studies. Issue 1 (27th June 2018) - Gladman, Dafna D; Kavanaugh, Arthur; Gómez-Reino, Juan J; Wollenhaupt, Jürgen; Cutolo, Maurizio; Schett, Georg; Lespessailles, Eric; Guerette, Benoit; Delev, Nikolay; Teng, Lichen; Edwards, Christopher J; Birbara, Charles A; et al.
Abstract : Objective: The Psoriatic Arthritis Long-term Assessment of Clinical Efficacy (PALACE) clinical trial programme findings demonstrated that apremilast, an oral phosphodiesterase 4 inhibitor, is effective for treating psoriatic arthritis (PsA). Enthesitis and dactylitis are difficult-to-treat features of PsA leading to disability and affecting quality of life. PALACE 1, 2 and 3 data were pooled to assess the efficacy of apremilast on enthesitis and dactylitis outcomes in patients with these conditions at baseline. Methods: Patients with enthesitis (n=945) or dactylitis (n=633) at baseline were analysed after receiving double-blind treatment with placebo, apremilast 30 mg two times per day or apremilast 20 mg two times per day up to 52 weeks and continuing up to 5 years. Data were analysed through 156 weeks. Enthesitis was evaluated by Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) and dactylitis via dactylitis count. Results: At week 24, patients receiving apremilast 30 mg two times per day demonstrated a significantly greater mean change in enthesitis (−1.3 vs −0.9; p<0.05) and dactylitis (−1.8 vs −1.3; p<0.01) vs placebo. Patients in the 30 mg dose group showed significantly greater mean (−23.6% vs −7.0%; p<0.05) and median (−50.0% vs −21.1%; p<0.05) per cent changes in MASES; mean and median per cent changes in dactylitis count were numerically, but not significantly, different for either apremilast dose in patients with dactylitis. In the patient population remaining on apremilast, observed mean and median improvements in both conditions were sustained through 156 weeks. Conclusion: Apremilast is effective for the treatment of active PsA, including improvements in enthesitis and dactylitis up to 3 years. Trial registration numbers: NCT01172938, NCT01212757 and NCT01212770 .